Glycerophospholipids protect stallion spermatozoa from oxidative damage in vitro. Issue 3 (11th August 2021) - Medica, Ashlee J; Aitken, Robert J; Nicolson, Garth L; Sheridan, Alecia R; Swegen, Aleona; De Iuliis, Geoffry N; Gibb, Zamira
Abstract : Stallion sperm membranes comprise a high proportion of polyunsaturated fatty acids, making stallion spermatozoa especially vulnerable to peroxidative damage from reactive oxygen species generated as a by-product of cell metabolism. Membrane lipid replacement therapy with glycerophospholipid (GPL) mixtures has been shown to reduce oxidative damage in vitro and in vivo . The aims of this study were to test the effects of a commercial preparation of GPL, NTFactor ® Lipids, on stallion spermatozoa under oxidative stress. When oxidative damage was induced by the addition of arachidonic acid to stallion spermatozoa, the subsequent addition of GPL reduced the percentage of 4-hydroxynonenal (4-HNE; a key end product of lipid peroxidation) positive cells (32.9 ± 2.7 vs 20.9 ± 2.3%; P ≤ 0.05) and increased the concentration of 4-HNE within the spent media (0.026 ± 0.003 vs 0.039 ± 0.004 µg/mL; P ≤ 0.001), suggesting that oxidized lipids had been replaced by exogenous GPL. Lipid replacement improved several motility parameters (total motility: 2.0 ± 1.0 vs 68.8 ± 2.9%; progressive motility: 0 ± 0 vs 19.3 ± 2.6%; straight line velocity: 9.5 ± 2.1 vs 50.9 ± 4.1 µm/s; curvilinear velocity: 40.8 ± 10 vs 160.7 ± 7.8 µm/s; average path velocity: 13.4 ± 2.9 vs 81.9 ± 5.9 µm/s; P ≤ 0.001), sperm viability (13.5 ± 2.9 vs 80.2 ± 1.6%; P ≤ 0.001) and reduced mitochondrial ROS generation (98.2 ± 0.6 vs 74.8 ± 6.1%; P ≤ 0.001). Supplementation with GPL during 17°C in vitro sperm storage over 72 h improved sperm viability (66.4 ± 2.6 vs 78.1 ± 2.9%; P ≤ 0.01) and total motility (53 ± 5.6 vs 66.3 ± 3.5%; P ≤ 0.05). It is concluded that incubation of stallion spermatozoa with sub-µm-sized GPL micelles results in the incorporation of exogenous GPL into sperm membranes, diminishing lipid peroxidation and improving sperm quality in vitro . Lay summary: Sperm collection and storage is an important step in many artificial insemination and in vitro fertilization regimes for several species, including humans and horses. The sperm membrane, which acts as a protective outer barrier, is made up of fatty acid-containing molecules – called phospholipids. These phospholipids may become damaged by waste products generated by the cell, such as hydrogen peroxide, during non-chilled sperm storage. We aimed to determine if sperm cells were able to repair this membrane damage by supplementing them with phospholipids during non-chilled storage. Sperm was collected from five miniature stallions by artificial vagina, and then supplemented with phospholipids during 72 h sperm storage at 17°C. Our studies show that when stallion sperm are supplemented with phospholipids in vitro, they are able to remove their damaged membrane phospholipids and swap them for undamaged ones, aiding in resistance to cellular waste and improving cell health and potential fertility.